TEXTUAL ANALYSIS BETWEEN HALAL AND HARAM ISLAMIC MUSIC BASED ON THE QURAN AND HADITH: English - Unyil unyil (Kawalu: Journal of Local Culture, 2023)
The understanding of the Qur'an and Hadith regarding music is still a matter of debate. Some scholars still insist that music is haram, on the other hand there are also scholars who say music is halal as long as it is still within positive limits. Therefore, the researcher conducted a textual analysis between Halal and Haram Islamic Music based on the Al-Quran and Hadith. This research was conducted with read, study, and analyze various existing literature, in the form of the Qur'an, hadith, and research results. By using a qualitative research approach, namely systematic research used to study or research an object on a natural setting without any manipulation in it and without there is a hypothesis test. The result of interpreting the hadith that prohibits music, textually will produce formative understanding and practice. That is, if you only rely on a hadith whose editorial forbids music, then enjoying music is haraam. However, in this case, the textual meaning cannot be practiced just like that because there are hadiths with other editors that allow music to be played. Thus, intertextual interpretation should not be carried out to find the message intended by the Prophet Muhammad. with the hadith. With intertextual meaning, it has a slight impact on extracting with contextual meaning, it results that substantially playing music is not an activity that is prohibited by the Prophet Muhammad SAW.